Quality II: A new paradigm for construction - Love, Peter; Matthews, J.; Porter, S.R.; Carey, Brad; Fang, W. (2023)
The Quality I paradigm utilizes an error prevention strategy to avert rework in construction. The effectiveness of this paradigm is questionable as rework has become an innate feature of practice. If rework is to be mitigated in construction projects, a new paradigm is needed to challenge conventional thinking and offer a different perspective on managing errors. We introduce a new paradigm, Quality II, by drawing on a narrative review, emerging best practices deployed in construction, and contemporary developments in safety (e.g., Safety II and III). The implications of a Quality II paradigm for theory development and practice are also examined. The contributions of this paper are twofold as we: (1) provide construction organizations with a new approach for managing and learning how to handle (i.e., learning through) errors, and thus provide them with the ability to adapt and respond to varying conditions effectively; and (2) align Quality II with contemporary safety paradigms to offset competing demands enabling construction organizations to maximize the use of their limited resources better. By curbing rework, the performance and productivity of projects and the profitability of construction organizations will improve.